Effect of an Educational Video Intervention on Anxiety Level among Patients prior to Cardiac Catheterization (Journal of Hama University, 2022)
Anxiety is one of the common problems that cardiac catheterization patients face. Which constitutes a real obstacle to the success of this important diagnostic procedure, and this Anxiety is often due to the lack of patient information about the cardiac catheterization procedure. Therefore, the current quasi-experimental study aimed to evaluate the effect of the educational video intervention on the level of anxiety in patients before performing cardiac catheterization, The study sample included 50 patients, who were randomly and equally divided into two groups (experimental and control). To determine the level of anxiety, the Beck Anxiety Inventory (BAI) questionnaire was used. as the results of the study showed that the level of anxiety in patients who were educated by an educational video before performing cardiac catheterization was lower than in those who were not educated by the video. The study recommended the necessity of adopting the educational video technique and intervention as a nursing procedure through which patients are educated and provided with the necessary information before performing cardiac catheterization, and conducting new studies on a wider sample.